The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1037/a0016354
|View full text |Cite
|
Sign up to set email alerts
|

The unique effect of paternal depressive symptoms on adolescent functioning: Associations with gender and father–adolescent relationship closeness.

Abstract: Prospective, longitudinal data from a community sample of 451 families were used to assess the unique contribution of paternal depressive symptoms to adolescent functioning. Results indicated that paternal depressive symptoms were significantly related to subsequent depressive symptoms in adolescent offspring; this association remained significant after controlling for previous adolescent depressive symptoms, maternal depressive symptoms, gender, and family demographic variables. Adolescent gender and percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 17 publications
6
33
0
Order By: Relevance
“…Our results, however, showed that financial deprivation did not moderate the effect of parental distress on youth emotional problems. This is in line with prior research showing that highly distressed parents report lower levels of their youths' well-being independently of socioeconomic deprivation (20,29,47,48). These results point to the complexity of understanding the association between parental distress and youth emotional well-being in an unemployment situation, which should go beyond financial deprivation to consider additional social variables (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Our results, however, showed that financial deprivation did not moderate the effect of parental distress on youth emotional problems. This is in line with prior research showing that highly distressed parents report lower levels of their youths' well-being independently of socioeconomic deprivation (20,29,47,48). These results point to the complexity of understanding the association between parental distress and youth emotional well-being in an unemployment situation, which should go beyond financial deprivation to consider additional social variables (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Another limitation is that only maternal MDD history was used to define risk groups. Paternal mental health also impacts offspring psychopathology risk, 54 as do other environmental factors such as exposure to trauma/stress; 55 however, given the current study’s sample size and recruitment design, it was not possible to investigate these sources of risk. Future studies actively investigating other sources of risk will be important for examining whether other risk factors relate to altered response to incentives.…”
Section: Discussionmentioning
confidence: 97%
“…Meta-analyses also find paternal depression is related to conflict in the father-child relationship (Kane and Garber 2004). Moreover, a recent prospective study found that after controlling for mothers' depression, fathers' depression was related to adolescents' depression only for girls who perceived low closeness in the father-child relationship (Reeb and Conger 2009). …”
Section: Fathersmentioning
confidence: 95%